مدى استقلالية مصرف البحرين المركزي وفقا للمعايير التشريعية - الطيب، عبدالجبار أحمد عبدالجبار (جامعة البحرين - كلية الحقوق, 2022)
تهدف هذه الدراسة إلى التعرف على جوانب الاستقلالية التي منحها المشرع في القانون رقم (٦٤) لسنة ٢٠٠٦ بإصدار قانون مصرف البحرين المركزي والمؤسسات المالية وتعديلاته للمصرف المركزي، وهي ما يطلق عليها (الاستقلالية التشريعية أو القانونية)، ومدى تماشيها مع المعايير والمقاييس التي وضعتها العديد من الدراسات الغربية والعربية، والتي تستهدف تحقيق أكبر قدر ممكن من الاستقلالية للبنوك المركزية. وعليه فتطرح هذه الدراسة موضوع الاستقلالية من خلال جانبين، يتمثل الأول فيما يمكن أن نسميه الاستقلالية التشريعية العامة وهي التي تتعلق باستقلالية مصرف البحرين المركزي في رسم وتنفيذ السياسة النقدية، واستقلاليته الإدارية والمالية، أما الجانب الآخر فيرتبط باستقلالية المصرف المركزي عن الحكومة، واستقلاليته في تحديد أهدافه وانتقاء وسائله وفيه يتم دراسة واقع الاستقلالية. ولأجل ذلك تم تقسيم هذه الدراسة لمبحثين رئيسين، على النحو التالي: المبحث الأول: الاستقلالية التشريعية لمصرف البحرين المركزي. المبحث الثاني: واقع استقلالية مصرف البحرين المركزي عن الحكومة. This study aims to identify the aspects of independence granted by the legislator in Law No. (64) of 2006 promulgating the Central Bank of Bahrain and Financial Institutions Law and its amendments to the Central Bank, which is called (legislative or legal independence), and the extent to which it conforms to the standards and those standards set by many Western and Arab studies; In order to achieve the greatest possible independence for central banks. Accordingly, this study raises the issue of independence through two aspects. The first is what can be called the general legislative independence, which is related to the independence of the Central Bank of Bahrain in formulating and implementing monetary policy, and its administrative and financial independence. The other aspect is related to the independence of the Central Bank from the government, and its independence in defining its objectives and selecting its means, in which the reality of independence is studied. For this reason, this study was divided into two main sections, they are: The first topic: The legislative independence of the Central Bank of Bahrain. The second topic: The reality of the independence of the Central Bank of Bahrain from the government.
Keywords: البنوك المركزية -- الاستقلالية التشريعية -- القانون المالي -- البحرين